Carriage of Multidrug Resistance Staphylococci in Shelter Dogs in Timisoara, Romania - János, Dégi; Viorel, Herman; Ionica, Iancu; Corina, Pascu; Tiana, Florea; Roxana, Dascălu (Antibiotics (Basel), 2021)
The present study aimed to determine the prevalence of Staphylococcus species, which pose risks for public health, by evaluating skin samples collected from dogs in an animal shelter in Timisoara. Skin samples were taken from 78 dogs, which were either clinically healthy or suffering from dermatological conditions. Staphylococcus spp. was isolated and recognized based on conventional methods based on colony appearance, microscopic morphology, sugar fermentation, and coagulase activity. Following biochemical analysis, Staphylococcus isolates were subject to PCR tests to detect sa-f and sa-r genes to confirm the isolates to genus level. The typical colonies were identified to species level using biochemical methods, namely the VITEK®2 ID-GP64 identification card (bioMerieux, France). The phenotypic antimicrobial resistance profiling was performed using the VITEK®2 AST GP Gram-positive specific bacteria card (bioMerieux, France). Forty-three samples were confirmed as positive for Staphylococcus spp. Staphylococcus isolates were classified into the following categories: S. aureus, S. pseudintermedius, S. intermedius, S. epidermitis, S. haemolyticus, and S. hyicus. Eight (18.60%, 8/43) out of all the samples harbored the mecA gene, highlighting the distribution among isolated staphylococcal species: Staphylococcus pseudintermedius (4/43, 9.30%), Staphylococcus intermedius (1/43, 2.32%) and Staphylococcus aureus (3/43, 9.30%), respectively. The phenomenon of resistance was present, to the following antimicrobial agents: erythromycin (38/43, 88.37%), benzylpenicillin, kanamycin, and tetracycline with 37 strains (37/43, 86.04%), gentamycin (30/43, 69.76%), chloramphenicol (29/43, 67.44%), trimethoprim/sulfamethoxazole (27/43, 62.79%), ampicillin (26/43, 60,46%), rifampicin (25/43, 58,13%), imipenem (14/43, 32,55%), nitrofurantoin (11/43, 25.58%), oxacillin (8/43, 18.60%), vancomycin (4/43, 9.30%) and clindamycin (3/43, 6.97%), respectively. The presence of multidrug-resistant zoonotic staphylococci in clinically healthy dogs and dogs with skin lesions is an animal health and human health concern.